Factors enabling community health workers and volunteers to overcome socio-cultural barriers to behaviour change: meta-synthesis using the concept of social capital - Nicole Mohajer; Debra Singh (BMC, 2018)
Abstract Background Community-based health workers and volunteers are not just low-level health workforce; their effectiveness is also due to their unique relationship with the community and is often attributed to social capital, an area not well studied or acknowledged in the literature. Methods A qualitative meta-synthesis was conducted using the SPIDER framework and based on critical interpretive synthesis. The protocol was registered with PROSPERO, ID = CRD42018084130. This article reports on the qualitative data extracted from the final 33 articles selected from 147 full-text articles on social capital and community-based health systems. Results Three constructs were identified that enable community health workers to bring about changes in behaviour in the community: seeing their role as a service or a calling motivated by altruistic values, accompanying community members on their journey and the aim of the journey being empowerment rather than health. Community health workers feel under-resourced to provide for expectations from the community, to fulfil their non-health needs, to meet the expectations of their employers and to be able to deliver health services. Conclusion The dichotomy of needs between the community and health services can be resolved if policy makers and programme designers examine the possibility of two cadres of community-based health workforce: full-time workers and part-time volunteers, with clear scopes of practice and supervision. Community health workers would primarily be concerned with task shifting roles demanded by programmes, and volunteers can focus on the wider empowerment-based needs of communities.